Perhitungan Estimasi Upaya Pengembangan Software Pulsa Online dengan Fuzzy C-Means dan Fuzzy K-Means - Tia Tanjung; Fenty Ariani; Wiwin Susanty; Arnes Yuli Vandika (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2022)
Top-up can be done by prepaid and postpaid. Top-up at this time can also be done by way of online purchases. Credit with a prepaid system is a real-time top-up. Payments are made before the customer uses credit. Prepaid credit is different from postpaid which is not real-time and is done after the customer uses credit. Before credit can be used, it is necessary to create a credit server first. In this case, limited resources become an obstacle in completing the credit server creation which will later be used by credit users. Therefore, it is necessary to estimate the effort in the development of the server application, so that the estimation can be known, both in terms of resources, and processing time to estimates in terms of costs. In this case, the appropriate method should be used to overcome the obstacle and reduce the risk of software development. There are several ways to use the Fuzzy K-Mean and Fuzzy C-Means methods to complete the creation of impulse servers, perform analysis and interpretation, and provide information and actions for the quality of research output, education, and evaluation research. The result of the grouping comparison is to produce a derivative formula for the Fuzzy K-Mean and Fuzzy C-Means algorithms.